Variations in Cerebral Arterial Circle of Willis in Patients With Hemorrhagic Stroke: A Computed Tomography Angiographic Study - HinaSiddiqi, TahrimAnsar, SamirFasih (Journal of Rawalpindi Medical College, 2013)
Background: To identify the anatomical variations in cerebral arterial circle of Willis in patients with hemorrhagic stroke. Methods: Computerized tomographic (CT) angiograms of fifty four non-randomly selected patients who presented with hemorrhagic stroke were studied for the anatomical variations in the circle of Willis regarding its completeness, pattern and symmetry. The individual cerebral vessels were also noted for the presence, origin, caliber and symmetry. The variations of the circle as whole and segmental variations were studied. Results: In the study, seventeen (31.4%) of fifty four (100%) cerebral arterial circles were complete. Eleven (20.3%) had typical configuration, nine (16.6%) had symmetrical and forty seven subjects (87%) had different types of variations in their component vessels. Variations are most common in posterior communicating artery followed by anterior communicating. Eleven (20.3%) circles were found with aneurysm. Conclusions: Different types of variations in the formation of circle of Willis as a whole and in its component vessels are common in patients of hemorrhagic stroke.